2021
DOI: 10.7554/elife.61797
|View full text |Cite
|
Sign up to set email alerts
|

The human origin recognition complex is essential for pre-RC assembly, mitosis, and maintenance of nuclear structure

Abstract: The Origin Recognition Complex (ORC) cooperates with CDC6, MCM2-7, and CDT1 to form pre-RC complexes at origins of DNA replication. Here, using tiling-sgRNA CRISPR screens, we report that each subunit of ORC and CDC6 is essential in human cells. Using an auxin-inducible degradation system, we created stable cell lines capable of ablating ORC2 rapidly, revealing multiple cell division cycle phenotypes. The primary defects in the absence of ORC2 were cells encountering difficulty in initiating DNA replication or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 133 publications
(159 reference statements)
3
20
0
Order By: Relevance
“…However, H2A.Z, which is implicated in hORC recruitment 45 , is enriched at the borders and distributed throughout the early MCM-DH clusters (Figure 6I). These results support the notion that hORC together with H2A.Z play a pivotal role in the iterative loading of the hMCM-DHs within the entire IZs 45,46 . In relation to transcriptional landscapes as shown by the available phosphorylated RNA Pol II ChIP-seq data 47 (Figure 6G) and global run-on sequencing (GRO-seq) data 48 (Figure S7I), our MCM-DH-bound sequences in early RDs are mapped in regions devoid of active transcription, which is also in agreement with previous genomic studies 49 .…”
Section: Global Landscape Of the Mcm-dh Footprintssupporting
confidence: 86%
“…However, H2A.Z, which is implicated in hORC recruitment 45 , is enriched at the borders and distributed throughout the early MCM-DH clusters (Figure 6I). These results support the notion that hORC together with H2A.Z play a pivotal role in the iterative loading of the hMCM-DHs within the entire IZs 45,46 . In relation to transcriptional landscapes as shown by the available phosphorylated RNA Pol II ChIP-seq data 47 (Figure 6G) and global run-on sequencing (GRO-seq) data 48 (Figure S7I), our MCM-DH-bound sequences in early RDs are mapped in regions devoid of active transcription, which is also in agreement with previous genomic studies 49 .…”
Section: Global Landscape Of the Mcm-dh Footprintssupporting
confidence: 86%
“…Recently, researchers using the CRISPR approach to knockout human Orc1, Orc2, Orc5, and Orc2/Orc5 reported that human core ORC is dispensable for replication ( 20 , 50 ). Meanwhile, findings from another study continue to suggest the essentiality of ORC using ORC-specific CRISPR screens ( 51 ). In human cells, acute depletion of Orc1 and Orc2 resulted in defects in the chromatin loading of MCMs.…”
Section: Discussionmentioning
confidence: 99%
“…We are also intrigued by the apparent slowing of euchromatin loading between early G1 and later G1 times. It is possible that a passive mechanism improves MCM loading in heterochromatin later in G1 phase because the more accessible euchromatin sites are already occupied [76][77][78] .…”
Section: Discussionmentioning
confidence: 99%